ANALYSIS OF THE SELF-CONCEPT OF INMATES IN THE CLASS II A WOMEN'S PRISON PALEMBANG - Kurnia Zaitiwi; Lena Marianti; Neni Noviza (LP2M IAI Al-Khairat Pamekasan, 2026)
This study describes the Analysis of the LGBT Self-Concept of Assisted Residents in the Class II A Women's Prison in Palembang. This research aims to describe the self-concept of the assisted residents who have a lesbian identity. This research method is a field research approach to descriptive qualitative research. Data collection tools are in the form of observations, in-depth interviews, and documentation. Meanwhile, the data analysis technique involves data reduction, data presentation, and conclusions. The subjects of this study are 4 inmates who are in the category of lesbian Butcy and Femme. In essence, self-concept has not existed since birth; self-concept is formed and developed gradually. This will be processed and captured through social contacts and other people around them. After conducting in-depth interviews to identify the results of self-concept in lesbian inmates in women's prisons, from various categories of lesbians, there are negative and positive self-concepts from the formation of this self-concept because there are factors that affect their self-concept as lesbians, such as the support of those around them and their acceptance of themselves.